Kinematic links between elements of the caterpillar drive of the tracked military vehicle - S. V. Baglaychuk; V. A. Nekhaev; V. А. Nikolaev (Вестник СибАДИ)
On the analysis’ basis of the dynamic processes (continuous (vibratory) and pulsed (striking)) occurring in caterpillar drive and stringing system of the tracked military vehicle, when moving on rough terrain with different carrying capacity and a road bed’s profile, there are determined the equations of kinematic links of the driving wheel with a frame of the tracked machine; aligning wheel with a mechanism of the track’s tension; fastening balancing levers, torsions’ links with the tracked machine’s body.